Optimal Revascularization Strategy for Patients With ST-segment Elevation Myocardial Infarction and Multivessel Disease: A Pairwise and Network Meta-Analysis - Cui, Kongyong; Yin, Dong; Zhu, Chenggang; Yuan, Sheng; Wu, Shaoyu; Feng, Lei; Dou, Kefei (Frontiers in Cardiovascular Medicine, 2022)
Background: The relative benefit of immediate complete revascularization, staged complete revascularization, and culprit-only percutaneous coronary intervention (PCI) remains unclear in hemodynamically stable patients with ST-segment elevation myocardial infarction (STEMI) and multivessel disease. The aim of this study was to compare the clinical outcomes of the 3 PCI strategies in this population. Methods: We followed a pre-specified protocol (PROSPERO number: CRD42020183801). A comprehensive search of the electronic databases including PubMed, EMBASE and Cochrane Library from inception through February 21, 2020 was conducted. Randomized trials evaluating the comparative efficacy and safety of at least 2 of the 3 PCI strategies were identified. The primary endpoint was the composite of cardiovascular mortality or myocardial infarction (MI) during the longest follow-up. Pairwise and network meta-analyses were performed with random-effects model. Results: Eleven trials including 6,942 patients were analyzed. Pairwise meta-analysis noted that immediate complete revascularization and staged complete revascularization were respectively associated with a 52% and 27% reduction in the risk of cardiovascular death or MI (relative risk [RR] 0.48, 95% confidence interval [CI] 0.32-0.73, I2=0%; and RR 0.73, 95% CI 0.61-0.88, I2=0%, respectively), compared with culprit-only PCI. The risk of cardiovascular death or MI was not statistically different in staged and immediate complete revascularization groups (RR 0.88, 95% CI 0.45-1.72, I2=0%). Network meta-analysis obtained almost similar results compared with pairwise meta-analysis, and immediate complete revascularization had a 77% probability of being the best strategy for reducing cardiovascular death or MI among the 3 PCI strategies. Conclusion: The current evidence suggests that both immediate and staged complete revascularization were associated with a reduction of cardiovascular death or MI compared with culprit-only PCI. Further trials are warranted to directly compare immediate versus staged complete revascularization in this population.